Cigarette smoke condensate promotes pro‐tumourigenic stromal–epithelial interactions by suppressing miR‐145. (23rd November 2012) - Pal, A.; Melling, G.; Hinsley, E. E.; Kabir, T. D.; Colley, H. E.; Murdoch, C.; Lambert, D. W.
<x xml:space="preserve">Abstract</x> Background Exposure to factors released from tobacco during chewing or smoking is recognized as a major risk factor for oral carcinogenesis and influences the phenotype of oral epithelial cells and fibroblasts within the underlying stroma. Micro(mi)RNA can regulate the expression of genes within cells, and previous studies show that tobacco products can alter the miRNA profiles in lung epithelial cells. However, the molecular alterations occurring in oral fibroblasts exposed to tobacco constituents remain to be elucidated. Methods Oral fibroblasts were exposed to cigarette smoke condensate (CSC) and miRNA expression compared to untreated controls using tiling low‐density arrays (TLDA). Expression of miRNA‐145 was confirmed by quantitative (q)RT‐PCR. The effect of CSC on fibroblast cell viability, motility and matrix metalloproteinase (MMP)‐2 expression was measured using MTS, a wound scratch assay and qRT‐PCR, respectively. Oral cancer cell migration in response to culture supernatants from mock, control or pre‐miR‐145‐transfected CSC‐treated fibroblasts was analysed by chemotaxis assay. Results TLDA analysis identified widespread changes in the miRNA expression profile of fibroblasts exposed to CSC. Pri‐, pre‐ and mature miRNA‐145 were significantly down‐regulated in response to CSC, and this was accompanied by up‐regulated expression of MMP‐2 and increased migration of fibroblasts compared to untreated controls. Re‐expression of miR‐145 abrogated the ability of fibroblasts to promote oral cancer cell chemotaxis in response to CSC. Conclusion These findings suggest that tobacco constituents influence the expression of miRNA within oral fibroblasts promoting a phenotype that increases oral cancer migration and sheds new light on the mechanisms underlying oral cancer pathogenesis.